Awareness towards personal risk among employees at MISC Berhad, Kuala Lumpur / Aina Syafiqa Abdul Razak - Abdul Razak, Aina Syafiqa (Faculty of Business and Management, 2017)
This research is to investigate the level of awareness personal risk among employees at MISC Berhad, Kuala Lumpur. This research was conducted to determine the significance relationship between job safety, coworker safety and management safety practices with the level of awareness towards personal risk. A total of one hundred (100) questionnaires were distributed among employees at MISC Berhad, Kuala Lumpur and eighty (80) questionnaires were completed and obtained. The study shows that job safety, coworker safety and management safety practices were important in influencing the level of awareness towards personal risk. Therefore, MISC Berhad, Kuala Lumpur needs to consider these factors and provide best solutions to increase the level of awareness among employees at the organizational.